(untitled) (Damascus University Journal for the economic and Political sciences, 2022)
Since the declaration of its founding, China is considered as one of the most countries in the world that provided support to the Palestinian cause, as the Chinese ideology followed during the period following the establishment stage in 1949 played an important role in directing that support, while China aborted any Israeli attempt to establish joint relations, With it. However, this policy began to take a different grant during the period that followed the stage of economic openness in China, where the Sino-Israeli relations witnessed many developments, and reached the level of economic and military dependence after the establishment of official relations between the two parties in 1992, and this fundamentally affected the Sino-Palestinian relations, and on Chinese policy to support the Palestinian cause and the legitimate rights of the Palestinian people.